Hospitalizations for congenital syphilis in children under one year old in the state of Pará, Brazilian Amazon: ecological study - Débora Talitha Neri; Amanda Loyse da Costa Miranda; Eliã Pinheiro Botelho; Rubenilson Caldas Valois; Geyse Aline Rodrigues Dias; Andressa Tavares Parente; Eliete da Cunha Araújo; Glenda Roberta Oliveira Naiff Ferreira (BMC, 2023)
Abstract Background The high incidence of congenital syphilis shows flaws in the resolution of primary health care, being a predictor of greater use of hospital services, whose regional differences in access to health actions and services may be reflected in health inequalities. Objective to investigate hospitalizations due to congenital syphilis in children under one year of age, in the state of Pará, Brazilian Amazon. Methods an ecological study was carried out, using hospitalization, lethality and mortality rates related to congenital syphilis in children under one year of age. Temporal analysis and mapping of hospitalization flows were carried out using Joinpoint®, version 4.7.0.0, Terraview 4.2.2, Tabwin 4.1.5. Results A total of 6,487 hospitalizations were recorded. For the ten years of the study period (2009 to 2018), the lethality rate showed a decreasing trend of - 13.5% (p = 0.01). The crude hospitalization rate showed an increasing trend of 12.8% (p < 0.000. The regression analysis demonstrated that there was a change point in the trend with a significant growth of 12.8% until 2016 (p = 0.0006). In the mortality rate the trend was stable (p = 0.56). The analysis of hospitalization care flows made it possible to identify that most hospitalizations due to congenital syphilis occurred in the municipalities of residence, but 1,378 (21.2%) had to move. Two large care gaps were highlighted in Metropolitan health regions II and III, belonging to macroregion II. The hospitalizations of residents of these regions were carried out by the assistance networks of Belém (capital) and Marituba, both of which are part of Metropolitana I. Residents of macroregions III and IV had the greatest distances traveled to access hospital care. Conclusions The increase in the rate of hospitalizations with an increasing trend demonstrates the impact that syphilis still causes in Brazil, not being resolved even after national government interventions in primary health care, but there was a decreasing trend in the fatality rate. The results demonstrate a heterogeneous organization of health care networks in the state's health regions and macroregions.